Water quality and recreational use of public waterways - Breen, Benjamin; Curtis, John; Hynes, Stephen (Journal of environmental economics and policy, 2018)
This study combines routinely collected water quality data from Ireland and an on-site survey of waterway users to evaluate whether trip duration is responsive to changes in water quality. Four categories of recreational users are considered: anglers, boaters, other water sports (e.g. rowing, swimming, canoeing, etc.) and land-based activities at water sites, specifically walking and cycling. Water quality measures included in the analysis include Water Framework Directive (WFD) status, biochemical oxygen demand, ammonia, phosphorus and faecal coliform. The analysis finds evidence that higher levels of recreational demand (i.e. trips of longer duration) occur at sites with better water quality. However, we also find no statistical association between the overall WFD status and the duration of the recreational trip, which indicates that WFD status is of limited practical use for recreational users.